Christian Faith, Intellectual Disability, and the Mere Difference/Bad Difference Debate - Gould, James B. (Philosophy & theology, 2018)
The mere difference view, endorsed by some philosophers and Christian scholars, claims that disability by itself does not make a person worse off on balance - any negative impacts on overall welfare are due to social injustice. This article defends the bad difference view - some disability is bad not simply because of social arrangements but because of biological deficits that, by themselves, make a person worse off. It argues that the mere difference view contradicts core doctrines of Christian faith. The analysis focuses on intellectual rather than physical or sensory disabilities.